Decision-making Tools and Memetic Algorithms in Management and Linear Programming Problems - Lesaca, Jesús M. Larrañaga; Guerrero, Ekaitz Zulueta; Ubis, Fernando Elizagarate; Bernardo, Jon Alzola (Revista de Management Comparat International, 2011)
Operational Research uses a set of tools based on scientific research principles to achieve rational and meaningful management decisions. This article tries to give solution to a highly complex Linear Programming problem by using Simplex method, Solver and a hybrid prototype which combines the theories of Genetic Algorithms with a new local search heuristic technique. Hybridization of these two techniques is becoming known as Memetic Algorithm. Additionally, this article tries to present different techniques to support management decision-making, with the intention of being used increasingly in the business environment sustaining, thus, decisions by mathematics or artificial intelligence and not only by experience.